Effects of inequality of supply hours on consumers’ coping strategies and perceptions of intermittent water supply in Kathmandu Valley, Nepal - B. Guragai (2018)
© 2017 Elsevier B.V. To investigate the effects of unequal supply hours on consumers’ coping strategies and perceptions of the intermittent water supply (IWS) in the Kathmandu Valley (KV), Nepal we conducted a randomized household survey (n = 369) and on-site water quality tests. Half of the households received piped water for 6 or fewer hours per week. To augment or cope with the inadequate supply, 28% of the households used highly contaminated and expensive tanker-delivered water. Half of the piped water samples (n = 13) were contaminated with Escherichia coli. Free chlorine concentration in all piped water samples was below the national standards (0.1–0.2 mg/L), but combined chlorine was detected at an average of 0.24 mg/L, indicating ingression of contaminants in the network. Point-of-use devices could increase access to safe water in the KV from 42% to 80%. The use of Lorenz curves and Gini coefficients revealed inequality of piped water supply hours per week both between and within service areas in the KV, due mainly to a small percentage of households who receive longer supply hours. To cope with reduced supply hours, home owners pay more to get water from alternative sources, while tenants compromise their water consumption. Under IWS, expectations for improvements in piped water quality and supply regularity are higher than those for supply volume. Consumers’ perceptions of the piped water services worsen with the reduction in supply hours, but perceptions of piped water tariff are independent of supply hours.